FERTILITY TREATMENT RESPONSE: IS IT BETTER TO BE MORE OPTIMISTIC OR LESS PESSIMISTIC? - Bleil, Maria E. (2012)
OBJECTIVE: To evaluate the prospective relation between dispositional traits of optimism and pessimism and IVF treatment failure among women seeking medical intervention for infertility. METHODS: Among 198 women (ages 24-45, M=35.1[4.1]; 77% white), the outcome of each participant’s first IVF treatment cycle was examined. Treatment outcome was classified as being successful (vs. failed) if the woman either delivered a baby or was pregnant as a result of the cycle by the end of the 18-month study period. At baseline, optimism and pessimism were measured as a single bipolar dimension and as separate unipolar dimensions according to the Life Orientation Test (LOT) total score and the optimism and pessimism subscale scores, respectively. RESULTS: Optimism/pessimism, measured as a single bipolar dimension, predicted IVF treatment failure initially (B = -.09; p = .02; OR = 0.917; 95% CI = 0.851 – 0.988), but this association attenuated following statistical control for trait negative affect (B = -.06; p = .13; OR = 0.938; 95% CI = 0.863 – 1.020). When examined as separate unipolar dimensions, pessimism (B = .14; p = .04; OR = 1.146; 95% CI = 1.008 – 1.303), but not optimism (B = -.09; p = .12; OR = 0.912; 95% CI = 0.813 – 1.023), predicted IVF treatment failure independently of risk factors for poor IVF treatment response as well as trait negative affect. CONCLUSIONS: Being pessimistic may be a risk factor for IVF treatment failure. Future research should attempt to delineate the biological and behavioral mechanisms by which pessimism may negatively affect treatment outcomes.